A review on status and profitability of large cardamom production in Nepal - Mohan Acharya (Goodwood Publishing, 2019)
Purpose: This study focuses on the status, strength and problems of large cardamom cultivation in Nepal and also identify profitability of large cardamom farming in Nepal. Research Methodology: Numbers of journal articles and reports were consulted as secondary source of data and conclusion were drawn and summarized. Results: Area and production of large caradamom in Nepal is increasing day by day and major production is concentrated in four eastern districts . B/C ratio of cardamom production varies from 1.70 to 3.06 and one fifth of household income in eastern hill of Nepal is attributed by Large cardamom. Price fluctuation, middleman and diseases are identified as major problems. Limitation: Lack of funding, less access to the data and documents are the limitations of study. Keywords: Status, B/C ratio, Profitability, Price fluctuation, Middleman How to Cite: Acharya, Mohan. (2019). A review on status and profitability of large cardamom production in Nepal. International Journal of Financial, Accounting, and Management, 1(1), 17-22.